Aflatoxin analysis in dried red pepper samples by TLC and HPLC - (:unkn) unknown (My University, 1998)
In this study, aflatoxins (AFLs) B1, B2, G1 and G2 were determined in dried red pepper samples provided from markets, street bazaars and spice- sellers in Istanbul, using thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). The number of samples used in the analysis by TLC, HPLC and both methods were 27, 5 and 6 respectively. The results from TLC and HPLC studies were compared. In Turkey the recommended limits for AFLB1 ise 5 ppb and total AFLs level is 20 ppb. In this research, aflatoxin B1 levels were higher than 5 ppb in about 50% of the samples and total AFL levels were ≥ 20 ppb in about 40% of samples.
Keywords: Aflatoxin; HPLC; Red pepper; Spices; TLC